Monimiaceae endémicas del Perú - León, Blanca (2006)
The Monimiaceae are represented in Peru by two genera and approximately 60 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004; Renner & Hausner, 2005), all shrubs and trees. Here we recognize two endemic species in two genera. These endemic species of Monimiaceae are found in Very Humid Premontane Forests and Humid Lowland Amazonian Forests regions, between 140 and 1800 m elevation. No endemic Monimiaceae have been registered today within Peru’s protected areas system.